IMPACT OF ILLEGAL GOLD MINING ( PETI ) TOWARD ENTERPRISES OF FISH FARMING IN PONDS IN THE SAWAH VILLAGE KUANTAN TENGAH DISTRICT, KUANTAN SINGINGI REGENCY RIAU PROVINCE - hendri, Ridar; ', Ramliyus; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in November 2014 in the Sawah Village, KuantanTengah District, Kuantan Singingi Regency, Riau province . This research aims : 1 ) todetermine the pond area before and after the PETI . 2 ) to determine the production of fishbefore and after the PETI .Population in this study is that fish farmers amounted to 14 people and 4 peopleinformant. So that the sample collection method using census method . PETI presence causesextensive pool down 34% from 10.410 m2 (43 units) to 6.860 m2 (28 units). PETI presencecauses fish production decreased 41 % from 110.400 kg to 64.050 kg/year. This is becausethe pond fish farmers polluted by waste dumped by illegal mining activities.Keywords: PETI, extensive pond fish farmers, fish production.